Working the relations of gender and the women history at the teaching practices - Janine Corrêa Gomes; Graziela Rinaldi da Rosa (Universidade Federal do Norte do Tocantins, 2020)
The idea of performing the First and the Second Seminars on Countryside and City Women of São Lourenço do Sul/Rio Grande do Sul, in 2015 and 2016, arises from a local need to think about public policies for rural and urban women. In this sense it has been tried to think of the diversity and the specificities of women and women's groups, existing in the municipality. In the First Seminar, held at the FURG/SLS Campus, it was provided a broad debate with an academic community and Lourenciana community, on issues related to women's health, work, violence against women, human rights and especially Education rights. So, in this first event, issues related specifically to countryside and city women were discussed. In the Second Seminar, it was possible to discuss prejudices and racisms, experienced by Pomeranian, black, quilombola, farmer, indigenous, riverine and transsexual women. In this seminar, it was aimed to hold an event that discussed with the academic community of the FURG/SLS Campus and with the Lourenciana Community, to think about the prejudice among us, empowerment and strengthening among us women, and women's groups in the city of São Lourenço do Sul and region. The thinking about prejudices, including the woman to woman. Both events sought to highlight a broader look at gender, feminism, rights, violence and education issues. Building and contributing to these women, regardless of race or ethnicity, to have a vision of importance and beauty as women, Opening a field for empowerment and for exchanges of more knowledge.